Reliability analysis of smart home sensor systems subject to competing failures - Wang, Chaonan; Liu, Qiongyang; Xing, Liudong; Guan, Quanlong; Yang, Chunhui; Yu, Min (Reliability engineering & system safety, 2022)
•A combinatorial method for reliability analysis of smart home sensor systems subject to competing failures.•The method is based on an efficient binary decision diagram reduction technique.•The method is applicable to any arbitrary component time-to-failure distribution.•Accuracy and efficiency are verified and compared with the fault tree reduction method. ZigBee and Bluetooth devices (particularly sensors) abound in smart home sensor systems (SHSSs), and they can only be connected to the network through gateways. Therefore, there exists functional dependence between these sensors and the corresponding gateway, where the failure of the gateway makes the connected sensors inaccessible or isolated. Two kinds of sensor failures can be distinguished in the SHSS: local failure that only affects the sensor itself (e.g., hardware failures) and propagated failure that affects other components and even causes the entire SHSS to fail (e.g., jamming attacks). Competitions exist between the gateway failure and propagated failures from the connected sensors in the time domain. Particularly, if the gateway fails before the propagated failures from the connected sensors, the propagated failures can be isolated and no longer affect other devices in the system; otherwise, the SHSS may fail due to the failure propagation effect. To address the influence of such competing failures, this paper proposes a new combinatorial method based on improved binary decision diagrams (BDDs) to analyze the reliability of SHSSs with competing failures. As compared to the existing method that involves generation of multiple reduced fault trees and their conversions to BDDs, the proposed method eliminates the process through an efficient BDD reduction technique. The efficiency and accuracy of the proposed method are discussed through an example SHSS.